Determinação de antibióticos macrolídeos sobre eletrodo impresso de carbono modificado com carbon black super P em sistema BIA-AMP - VELOSO, William Barros (2021)
Macrolides are a group of drugs used in the treatment of infectious diseases, both in human and veterinary medicine. Currently these molecules are among the four most used antimicrobials in the world. The presence of these compounds in inadequate concentrations can be a trigger to a series of problems both directly and indirectly, such as allergic reactions in sensitive individuals and the emergence of resistant strains of bacteria. This work investigated the potential application of carbon black Super P as a modifier for screen-printed carbon electrodes (SPCE’s) in a Batch Injection Analysis system with Amperometric detection (BIA-AMP) to determine four macrolide antibiotics (erythromycin, azithromycin, clarithromycin and roxithromycin). Previous modifier’s parameters optimization have shown that the ideal carbon black concentration and suspension volume are, respectively, 7.0 mg mL-1 and 10 µL. Initial voltammetric studies carried out with erythromycin, a prototype compound, demonstrated the redox process characteristics of this class of antibiotics. In addition, it was also possible to define the support electrolyte (Sörensen buffer) and pH of the medium (7.8) ideal for the development of the method. Hydrodynamic voltamograms respective to each antibiotics were constructed to define the work potential used in all amperometric measurements. BIA system parameters optimization showed ideal values respectively equal to: injection volume (100 µL) and dispensing speed (100 µL s-1). Under these conditions, a precision study was carried out to obtain the DPR value of 0.983% (n = 25) and an analytical frequency estimated at 125 injections per hour. The proposed method presented a linear range of 1 - 190 µmol L-1 for erythromycin (R = 0.999), azithromycin (R = 0.998) and roxithromycin (R = 0.999) and 10 - 190 µmol L-1 for clarithromycin (R = 0.998). Thus, the method was applied to determine these four compounds in a water sample, collected in a pond located on the Federal University of Maranhão campus, and in pharmaceutical samples. Addition-recovery studies were performed on both samples, in which recovery values between 96.0 and 104.7% were obtained for the tests carried out on an environmental sample and between 95.6 and 105.1% for the tests carried out on medicine samples, proving the good accuracy of the method, which proved to be a verry attractive alternative from an economic and portability point of view.